Work Motivation as a Mediator of Career Development and Competency for Employee Performance at the Mojokerto City Regional Secretariat Office - Dewi, Tutik Ning Rahayu Surya; Nasir, M. Jamal Abdul; Farhan, Djuni (Enrichment: Journal of Multidisciplinary Research and Development, 2024)
This study aims to test and analyze the influence of: 1) career development on work motivation, 2) competence on work motivation, 3) career development on employee performance, 4) competence on employee performance, 5) work motivation on employee performance, 6) the influence of career development on employee performance through motivation, 7) motivation mediates the influence of competence on employee performance through motivation. Using an explanatory research approach, this research was conducted at the Mojokerto City Regional Secretariat Office in June-August 2023. The population is 109 civil servants in the Office. The sample was determined by saturated sample technique, as many as 108 such people (excluding the author). Primary data related to research variables were obtained by giving questionnaires directly to respondents. Once the data is collected, it is analyzed using path analysis. However, previously tests were carried out on validity, reliability and classical assumptions. To test the hypothesis used t-test and to determine motivation as a mediator used Sobel's test. The results proved that: 1) career development has a significant positive effect on work motivation, 2) competence has a significant positive effect on work motivation, 3) career development has a significant positive effect on employee performance, 4) competence has a significant positive effect on employee performance, 5) work motivation has a significant positive effect on employee performance, 6) work motivation is able to mediate/increase the influence of development career on employee performance, 7) work motivation is able to mediate/increase the influence of competence on employee performance.